Donor–Acceptor Cyanocarbazole‐Based Supramolecular Photocatalysts for Visible‐Light‐Driven H2 Production. Issue 23 (18th November 2019) - Zhang, Guoqiang; Yang, Xun; Li, Yongliang; Zhang, Peixin; Mi, Hongwei
Abstract: Highly efficient, stable, and metal‐free supramolecular photocatalysts for H2 production are uncommon and of significant interest. In this study, a donor–acceptor (D–A) cyanocarbazole‐based supramolecule (2CzPN) is assembled by intermolecular C≡N⋅⋅⋅H−Ar H‐bonding interactions to form an efficient, stable, and metal‐free photocatalyst for H2 evolution. The catalyst affords an H2 production rate of 91.8 μmol h −1 (20 mg of samples, λ >420 nm) and a corresponding apparent quantum efficiency of 7.5 % at 420 nm. The photon‐generated carrier separation of the 2CzPN supramolecule, which is higher than that of the analogous polymer, can be attributed to the strong D–A characteristics and high crystallinity. This study offers the first experimental evidence of visible‐light H2 evolution among D–A cyanocarbazole‐based supramolecules and it enriches the variety of supramolecular photocatalysts. This stable and effective metal‐free 2CzPN supramolecular photocatalyst has obvious advantages among very few supramolecular photocatalysts for H2 production. Abstract : A visible improvement : A donor–acceptor cyanocarbazole‐based supramolecule, assembled through intermolecular C≡N⋅⋅⋅H−Ar hydrogen‐bonding interactions, is found to be an efficient, stable, metal‐free photocatalyst for visible‐light H2 evolution. The catalyst affords an H2 production rate of 91.8 μmol h −1 ( λ >420 nm) and a corresponding apparent quantum efficiency (AQE) of 7.5 % at 420 nm.